STRATEGI PENGELOLAAN AGROWISATA KEBUN KOPI DI DESA PURWOREJO TIMUR, KABUPATEN BOLAANG MONGONDOW TIMUR - Hardiana Fujiadisti Paputungan; Zetly E. Tamod; Diane D. Pioh (AGRI-SOSIOEKONOMI, 2017)
This research is aimed at 1) obtaining a picture of socio-cultural profile, community economy, natural resources and environment in relation to design agro-tourism development in East Purworejo village as an agro-tourism destination; 2) to analyze and describe community perception and stakeholder in agro-tourism development in East Purworejo Village, and 3) arranging strategy that can be developed to create East Purworejo Village as a sustainable agro-tourism area. This problem is done by qualitative and quantitative descriptive approach also with SWOT analysis and Quantitative Strategic Planning Matrix (QSPM) method, data collection is based on questionnaire, observation, and in-depth interview on 72 respondents. Results of research indicate that society in East Purworejo Village area is society with good social relation, to become capital for agro development area of East Purworejo Village. The economic activities of the community in East Purworejo Village are dominated by agricultural activities that play an important role in village economic system. The ecosystems around the area of East Purworejo Village range from lakes, active mountain ecosystems, gardens and forests. Geographically, the area of East Purworejo agro is also close to the mountains that have potential to become objects and tourist destinations, such as Tondok Lake and Lake Moaat. The perception value of the respondents' responses to the design of agro-tourism development in East Purworejo area, according to the scale range is at an average of 4.67 for the community and stakeholders of 4.70; so the respondents have a positive perception towards to development of agro Garden Coffee in East Purworejo Village. Policy strategy through SWOT analysis to design agro-tourism development in East Purworejo area, that is internal factor obtained by difference of total score of strength with total score of weakness equal to 27, while external factor obtained by difference opportunity total score with total score of threat equal to 18.